Late Breaking Clinical Trials: Quetiapine as Potential First-Line Treatment in Acute Bipolar II Depression - Busse, Gregory (MD Conference Express, 2007)
Patients with bipolar II disorder can be particularly difficult to treat, as they are sensitive to the side effects of treatment and more susceptible to treatment-emergent rapid cycling and shifts in affect. Currently there is not enough evidence to select one agent over another in terms of first-line therapy. This article presents results of quetiapine monotherapy in the treatment of acute depression in patients with bipolar II disorder.